Pendampingan Pengelolaan Anggaran untuk Optimalisasi Realisasi Kegiatan BIMTEK di Bidang Pembinaan Koperasi: Studi Kasus Dinas Koperasi dan UKM Provinsi NTB Periode 2021–2023 - Dewi Rizqiyati Amalyah; Fanny Annisa Puspa Kirana; Gerindra Mulana Saputra; Himawan Sutanto (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Budget management is an important component in ensuring the success of government programs, such as Technical Guidance (Bimtek) at the NTB Provincial Cooperative and SME Service. The purpose of this article is to analyze the effectiveness of budget management related to the implementation of Bimtek activities in the field of cooperative development during the 2021–2023 period. The methods used include interviews with service employees, collection of budget and realization data, and comparative analysis related to planning and implementation each year. The results of the study showed a discrepancy between the planned and realized budgets, which was caused by problems such as late disbursement, codification, and complexity of the reporting system. Although most activities were successful with a success rate of 90%, especially in 2021 and 2023, there was a significant decline in efficiency and productivity in 2022. As a result, real-based planning, improved administration and reporting systems, and coordination between parties are essential to improve the effectiveness of budget management in ensuring the smooth implementation of Bimtek activities.